Good Practice Example and a Success Story from the European Commission - Theocharous, Antonis L. (My University, 2026)
Good Practice Example and a Success Story from the European Commission European Project Leonardo da Vinci (LdV)-Transfer of Innovation (TOI) project: “Ecotourism: New Knowledge by Innovation, New Jobs by Knowledge Transfer (ECOTOUR)” Awarded by European Project Leonardo da Vinci (LdV)-Transfer of Innovation (TOI) project
Keywords: Sciences